Distinct Distribution of Archaea From Soil to Freshwater to Estuary: Implications of Archaeal Composition and Function in Different Environments - Wang, Hualong; Bier, Raven; Zgleszewski, Laura; Peipoch, Marc; Omondi, Emmanuel; Mukherjee, Atanu; Chen, Feng; Zhang, Chuanlun; Kan, Jinjun (Frontiers in Microbiology, 2020)
In addition to inhabiting extreme territories, Archaea are widely distributed in common environments spanning from terrestrial to aquatic environments. This study investigated and compared archaeal community structures from three different habitats (representing distinct environments): agriculture soils (from farming system trials FST, PA, USA), freshwater biofilms (from White Clay Creek, PA, USA), and estuary water (Chesapeake Bay, USA). High-throughput sequencing of 16S rRNA genes indicated that Thaumarchaeota, Euryarchaeota, Nanoarchaeota, Crenarchaeota, and Diapherotrites were the commonly found dominant phyla across these three environments. Similar to Bacteria, distinct community structure and distribution patterns for Archaea were observed in soils vs. freshwater vs. estuary. However, the abundance, richness, evenness, and diversity of archaeal communities were significantly greater in soils than it was in freshwater and estuarine environments. Indicator species (or amplicon sequence variants, ASVs) were identified from different nitrogen and carbon cycling archaeal groups in soils (Nitrososphaerales, Nitrosotaleales, Nitrosopumilales, Methanomassiliicoccales, Lainarchaeales), freshwater biofilms (Methanobacteria, Nitrososphaerales) and Chesapeake Bay (Marine Group II, Nitrosopumilales), suggesting the habitat-specificity of their biogeochemical contributions to different environments. Distinct functional aspects of Archaea were also confirmed by functional predictions (PICRUSt2 analysis). Further, co-occurrence network analysis indicated that only soil Archaea formed stable modules. Keystone species (ASVs) were identified mainly from Methanomassiliicoccales, Nitrososphaerales, Nitrosopumilales. Overall, these results indicate a strong habitat-dependent distribution of Archaea and their functional partitions within the local environments.